The Power of Two : A Twin Triumph Over Cystic Fibrosis - Stenzel Byrnes, Isabel, 1972- (Book collections on Project MUSE., 2007)
"Born in 1972, twins who share this life-threatening disease give an honest portrayal of their struggle to live normal lives, their interdependence, day-to-day health care, the impact of chronic illness on marriage and family, and the importance of a support network to continuing survival"--Provided by publisher.